Medicinal Plants Used by Dayak Kanayatn Traditional Healers in Tonang Village Sengah Temila District Landak Regency - Rika Purnama Sari; Fathul Yusro; Yeni Mariani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Plants have an essential role in people's lives because of their benefits and properties, such as for medicinal properties. In Landak District, only limited studies on medicinal plant had been carried out. This study analyzes the species of medicinal plants used by the Dayak Kanayatn tribal traditional healers in Tonang Village, Sengah Temila District, Landak Regency. The sampling used the snowball sampling technique. The results found that traditional healers of Dayak Kanayatn in Tonang Village used a total of 60 species belong to 36 families. The most utilized families (8.47%) are Zingiberaceae and Asteraceae. The extensive use of plant habitus is herbs (41,67%). Leaves are the most dominant plant part used (44.78%), while the highest processing method was boiled (39.74%). The highest form of use was drinking (38.67%), the most common location of plants was in the yard (67.74%), the highest plant status is cultivated (52%), and the highest form of the potion is in the form of a mixture (72%). The result shows that the traditional healers in the Dayak Kanayatn community in Tonang Village, Sengah Temila District, Landak Regency, still use medicinal plants to overcome health problems and treat disease.